216k views
5 votes
Given: f(x) = 2x + 5 and g(x) = x2 and h(x) = -2x

h(g(f(x))) = ___ x²+ ___ x + ___

User Droj
by
5.9k points

2 Answers

5 votes

Answer:

-8

-40

-50

Explanation:

User MJZ
by
6.4k points
3 votes

For this case we have the following functions:


f (x) = 2x + 5\\g (x) = x ^ 2\\h (x) = - 2x

So, we have to by definition:


g (f (x)) = (2x + 5) ^ 2 = (2x) ^ 2 + 2 (2x) (5) + 5 ^ 2 = 4x ^ 2 + 20x + 25

So:
h (g (f (x))) = - 2 (4x ^ 2 + 20x + 25) = - 8x ^ 2-40x-50

We take common factor:


- (8x ^ 2 + 40x + 50)

Answer:


h (g (f (x))) = - (8x ^ 2 + 40x + 50)

User Holiday
by
6.0k points